1997
DOI: 10.1037/0278-7393.23.1.201
|View full text |Cite
|
Sign up to set email alerts
|

Hidden covariation detection might be very hidden indeed.

Abstract: have demonstrated that people can unconsciously detect and retain a nonsal lent covariation embedded within presented stimuli. In 9 conceptual replications of the hidden covariation detection (HCD) paradigm, there was little evidence for HCD. In exact replications of 3 of Lewicki's studies (T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
2
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(107 citation statements)
references
References 39 publications
1
100
2
4
Order By: Relevance
“…Cohen, et al, 1990;Lewicki, 1986;Lewicki, Hill, & Czyzewska, 1992. On the other hand, the result is consistent with recent findings that raise some doubts about the ubiquity and unavoidability of stimulus transition learning (Hendrickx, de Houwer, Baeyens, Eelen, & van Avermaet, 1997;Jime´nez & Me´ndez, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Cohen, et al, 1990;Lewicki, 1986;Lewicki, Hill, & Czyzewska, 1992. On the other hand, the result is consistent with recent findings that raise some doubts about the ubiquity and unavoidability of stimulus transition learning (Hendrickx, de Houwer, Baeyens, Eelen, & van Avermaet, 1997;Jime´nez & Me´ndez, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…When we excluded the 8 participants who mentioned sound from the analyses, the effect in Block 3 was no longer significant at the .01 level, t(54) ϭ 2.31, p Ͼ .024. Finally, we also considered the possibility that other covariates than the one investigated might coincidentally have contributed to the effect (i.e., correlated covariates; Hendrickx et al, 1997), perhaps even consciously. Some common characteristics between the names other than the vowels might have worked as such.…”
Section: Resultsmentioning
confidence: 99%
“…As Hendrickx et al (1997) have noted, a failure to detect only a few instances of explicit knowledge may directly influence the effect. Because it is impossible to be certain that all participants remained unaware at all times, the effect might be confounded by undetected awareness in some participants, which may cast some doubt on whether the HCD effect is based on unconscious processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implicit learning has also been observed in priming studies (Bodner & Masson, 2001Greenwald, Abrams, Naccache, & Stanislas, 2003;Jaskowski, Skalska, & Verleger, 2003), sequential learning studies (Destrebecqz & Cleeremans, 2001;Jiménez & Méndez, 1999;Mayr, 1996;Nissen & Bullemer, 1987), and object-location learning studies (Hoffmann & Kunde, 1999;Musen, 1996). Additionally, Lewicki (1986;Lewicki et al, 1992Lewicki et al, , 1997 reported various demonstrations of implicit covariation learning (cf., Hendrickx et al, 1997aHendrickx et al, , 1997b. Given all this data, implicit learning seems to be a highly replicable and general phenomenon (although there will always be some debate over what constitutes evidence of implicit learning; see Frensch & Rünger, 2003, for a discussion of these issues).…”
Section: Discussionmentioning
confidence: 96%